2008
DOI: 10.1007/s10600-009-9196-2
|View full text |Cite
|
Sign up to set email alerts
|

Anticoccidial constituents from the stem bark of Turraeanthus africanus

Abstract: In order to study some biological active products, phytochemical investigation of the stem bark of Turraeanthus africanus have led to the isolation of a novel compound 1, a new benzoic acid derivative, named turraeanthin C, and two known compounds sesamin (2) and stigmasterol. The structures of these compounds were established by spectral analysis, including two-dimensional nuclear magnetic resonance. The extract and the isolated compounds 1 and 2 showed noteworthy activity against Toxoplasma gondii intracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…are small trees, 3-5 m high, commonly distributed in tropical Africa. Previous studies of the genus have reported the isolation of diterpenes, triterpenes and alkaloids [3][4][5][6][7].…”
mentioning
confidence: 99%
“…are small trees, 3-5 m high, commonly distributed in tropical Africa. Previous studies of the genus have reported the isolation of diterpenes, triterpenes and alkaloids [3][4][5][6][7].…”
mentioning
confidence: 99%